Enhanced efficiency of thermally activated delayed fluorescence emitters by suitable substitution on isonicotinonitrile. (November 2019) - Islam, Amjad; Wang, Zhiheng; Ji, Shaomin; Usman, Khurram; Abbas, Syed Comail; Li, Jianguo; Chen, Lihui; Iqbal, Mudassir; Su, Shi-Jian; Ouyang, Xinhua
Abstract: Two novel thermally activated delayed fluorescence (TADF) emitters, 3, 5-bis(4-(9H-carbazol-9-yl)phenyl)Isonicotinonitrile (2CzP-INN) and 3, 5-bis(4-(di ([1, 1′-biphenyl]-4-yl)amino)phenyl)isonicotinonitrile (2BTPA-INN), have been developed and their photophysical, electrochemical and electroluminescent properties have also been studied. Both materials possess high thermal stabilities and high photoluminescence quantum yields (PLQYs). Importantly, organic light emitting device (OLED) with 2BTPA-INN as emitter showed outstanding performance with a low driven voltage (VON ) of 2.9 V, a high external quantum efficiency (EQE) of 26.1%, power efficiency (PE) of 93.7 lm/W and current efficiency (CE) of 83.7 cd/A, which is among the excellent performances for TADF OLEDs. The enhanced efficiency can be ascribed to the high PLQY. These results provide an optimum strategy to design efficient materials for TADF OLED devices. Graphical abstract: Image 1 Highlights: Isonicotinonitrile Based Emitters. Green Thermally Activated Delayed Fluorescence. High Photoluminescence Quantum Yield. High Efficiencies (26.1%, 83.7 cd/A, 93.7 lm/W).